Monitoring of taurine dietary supplementation effect on parameters of Duroc boar ejaculate in summer season - Pribilova, Magdalena; Skalickova, Sylvie; Urbankova, Lenka; Baholet, Daria; Nevrkla, Pavel; Kopec, Tomas; Slama, Petr; Horky, Pavel (PloS one, 2024)
The aim of this experiment was to find out whether the taurine supplementation in daily ration had an effect on quantity or quality of Duroc boar ejaculate. The experiment duration was from June to August, when it could assumed the possible occurrence of heat stress. For the study was chosen 12 Duroc boars of approximately the same age and condition. The control group of 6 Duroc boars was fed only by basic diet and the experimental group of 6 Duroc boars was fed by the same basic diet with supplementation of 15 g taurine/boar/day. Ejaculate was collected once a week by hand glowed technique. From ejaculate parameters were monitored volume of ejaculate, sperm concentration, total amount of sperm, morphologically abnormal sperm, taurine concentration and GSH/GSSH concentration. From microscopic analysis, results were statistically significant in motility in June and July (P<0.05). In biochemical results, a significant difference (P<0.05) has been found between the experimental groups in the concentrations of taurine as well as GSH/GSSG in ejaculate which indicates the effect of heat stress on boars during the experimental period.
Keywords: Dietary Supplements; analýza spermatu; sperma; Swine; Semen; Sperm Motility; Spermatozoa; roční období; Animals; spermie; motilita spermií; mužské pohlaví; Male; zvířata; prasata; Seasons; potravní doplňky; Semen Analysis